Porous coral reefs-like MoS2/nitrogen-doped bio-carbon as an excellent Pt support/co-catalyst with promising catalytic activity and CO-tolerance for methanol oxidation reaction. (20th August 2017) - Tang, Bo; Lin, Yuhui; Xing, Zipeng; Duan, Yaqiang; Pan, Siyu; Dai, Ying; Yu, Jia; Zou, Jinlong
Graphical abstract: Highlights: Pt/MoS2 /CNX yields promising catalytic activity for methanol oxidation reaction. CNX skeleton affords abundant binding sites for growing well-dispersed MoS2 sheets. MoS2 /CNX provides more sites to anchor Pt to enlarge electrochemically active area. The OH species on MoS2 /CNX is favorable for striping off CO-intermediates on Pt. Abundant active sites of MoS2 /CNX derived from skeleton defects enhance CO tolerance. Abstract: The problems of poor electrocatalytic activity and CO tolerance and high Pt-loading of the Pt-based catalysts are still needed to be solved for direct methanol fuel cells. In this study, porous MoS2 /nitrogen-doped carbon (MoS2 /CNX ) as Pt supports/co-catalyst for methanol oxidation reaction (MOR) is successfully prepared by using waste bagasse as carbon source. Various material characterization techniques and electrochemical tests are performed to investigate the relationship between structural characteristics and MOR activity. The highly porous structure of CNX can provide abundant binding sites for growing well-dispersed MoS2 with coral-reef structure, which should facilitate the exposure of MoS2 edge to improve co-catalytic activity of MoS2 /CNX . Pt/MoS2 /CNX displays a higher mass activity (1030.2 mA mgpt −1 ) than those of Pt/MoS2 /C (710.1 mA mgpt −1 ) and commercial Pt/C (405.4 mA mgpt −1 ), owing to that MoS2 /CNX can afford abundant attachment sites to anchor Pt to enlarge the available electrochemically active area (111.2 m 2 g −1 pt ) for MOR. With the introduction of porous CNX, more active sites on MoS2 edges are exposed out to dissociate water molecule for eliminating adsorbed CO-species on the active sites of Pt, which is conductive to enhance the durability and CO tolerance of Pt/MoS2 /CNX . Furthermore, MoS2 /CNX with high specific surface area (451.38 m 2 g −1 ) can offer sufficient oxygen-containing functional groups to facilitate the oxidation of intermediates (CO-species) on the active Pt sites, which can also promote the accessibility of methanol to the electroactive surface. These results provide a promising strategy for the design of highly active Pt support/co-catalyst to minimize Pt usage.